POM-catalyzed in situ ligand synthesis for the construction of metal complexes and their use in the formation of coordination polymers - Dey, Chandan; Banerjee, Rahul (Chemphyschem, 2013)
Six organicinorganic hybrid materials were synthesized by the in situ oxidation of neocuproine by using MoO3/Na2MoO4 as the catalyst in the presence of Cu(NO3)2. The crystal structures of Mo8-Cu4-PHEN and Mo8-Cu2-5(2PIC) are composed of [Mo8O26]4 polyoxometalate (POM) units, whereas the crystal structure of Mo6-Cu-COPHEN is composed of a [Mo6O19]2 POM unit; both POM units could be considered as the active form of the catalyst. Reaction of the hybrid materials with 1,3,5-benzenetricarboxylic acid (BTC) resulted in the formation of two different coordination polymers (CPs) under different reaction conditions. These CPs, depending on their structural attributes, exhibit distinct differences in the adsorption of H2, CO2, and water. The use of 2-methylpyridine instead of neocuproine does not give any oxidation products under the same reaction conditions due to the incorrect positioning of the methyl group with respect to the CuII center.
Keywords: coordination polymers; Copper; N ligands; organicinorganic hybrid composites; polyoxometalates